1998
DOI: 10.1023/a:1008065519820
|View full text |Cite
|
Sign up to set email alerts
|

Untitled

Abstract: A brief review of literature on sorghum for human foods and on the relationship among some kernel characteristics and food quality is presented. The chief foods prepared with sorghum, such as tortilla, porridge, couscous and baked goods are described. Tortillas, prepared with 75% of whole sorghum and 25% of yellow maize, are better than those prepared with whole sorghum alone. A porridge formulation with a 30:40:30 mix of sorghum, maize and cassava respectively, has been shown to be the most acceptable combina… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
23
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 103 publications
(25 citation statements)
references
References 8 publications
0
23
0
Order By: Relevance
“…However, sorghum is often regarded as a low-value crop for food and feed uses due to low digestibility of its protein and starch relative to other cereals. The low digestibility of sorghum protein is most pronounced in wet cooked foods (Axtell et al, 1981;Hamaker et al, 1986;Duodu et al, 2002) where protein digestibility decreases of up to 50% have been reported (Anglani, 1998;Duodu et al, 2003). The cause for poor digestibility of sorghum protein is not fully understood, but it is postulated to be multifactorial.…”
Section: Genetic Basis Of Protein Digestibility In Grain Sorghummentioning
confidence: 99%
“…However, sorghum is often regarded as a low-value crop for food and feed uses due to low digestibility of its protein and starch relative to other cereals. The low digestibility of sorghum protein is most pronounced in wet cooked foods (Axtell et al, 1981;Hamaker et al, 1986;Duodu et al, 2002) where protein digestibility decreases of up to 50% have been reported (Anglani, 1998;Duodu et al, 2003). The cause for poor digestibility of sorghum protein is not fully understood, but it is postulated to be multifactorial.…”
Section: Genetic Basis Of Protein Digestibility In Grain Sorghummentioning
confidence: 99%
“…It is a recommended cereal for those who suffer from celiac disease (gluten intolerance) and serves as a rich source of antioxidants (Anglani, 1998). It is ranked fifth in importance in terms of production and acreage, grown on 42 million hectares in ~105 countries in Asia, Africa, Oceania, and the Americas.…”
Section: Researchmentioning
confidence: 99%
“…It is ranked fifth in importance in terms of production and acreage, grown on 42 million hectares in ~105 countries in Asia, Africa, Oceania, and the Americas. It is a recommended cereal for those who suffer from celiac disease (gluten intolerance) and serves as a rich source of antioxidants (Anglani, 1998). In regions where rainfall is limited and irrigation is not affordable, sorghum is a good substitute for other cereals (Nedumaran et al, 2013;Reddy et al, 2012).…”
Section: Researchmentioning
confidence: 99%
“…Sorghum is also an important staple food for 500 million people in Asia and sub-Saharan Africa (Anglani, 1998). Its ability to tolerate periods of drought, high temperatures, and low inputs has made it a preferred cereal to grow in semi-arid climates.…”
Section: Introductionmentioning
confidence: 99%